2017
DOI: 10.31219/osf.io/nk334
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barriers to Multiculturalism: Ingroup Favoritism and Outgroup Hostility are Independently Associated with Policy Opposition

Abstract: Bias in favor of the ingroup is a key determinant of discrimination, and is thought to be largely independent of, and qualitatively distinct from, outgroup hostility. One key difference, according to Realistic Conflict Theory, is that ingroup preferences become more closely associated with discrimination when intergroup threat is salient. The current study presents a direct comparison of the level of association of ingroup favoritism and outgroup hostility with opposition to multiculturalism policies in New Ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(62 reference statements)
1
5
0
Order By: Relevance
“…Overall, respondents from this cross-sectional, opt-in study were positive towards immigrants in general and climate migrants specifically, including when accounting for differences in sample demographics. This positivity reflects previous findings about Aotearoa NZers' openness to cultural diversity (Perry et al 2018;Sibley and Ward 2013). However, people believed that immigrants more than climate migrants made positive contributions to society, even accounting for sample characteristics and different levels of belief in climate change (cf.…”
Section: Discussionsupporting
confidence: 85%
“…Overall, respondents from this cross-sectional, opt-in study were positive towards immigrants in general and climate migrants specifically, including when accounting for differences in sample demographics. This positivity reflects previous findings about Aotearoa NZers' openness to cultural diversity (Perry et al 2018;Sibley and Ward 2013). However, people believed that immigrants more than climate migrants made positive contributions to society, even accounting for sample characteristics and different levels of belief in climate change (cf.…”
Section: Discussionsupporting
confidence: 85%
“…Apathy is not a particularly potent motivator of behavior, except perhaps neglect (Cuddy et al, 2008;Vachon, Lynam, & Johnson, 2014). Given that (i) intergroup conflict is often beset with overt antipathy and (ii) decreased positive affect and increased negative affect towards out-groups can be independent predictors of attitudinal outcomes (Perry, Priest, Paradies, Barlow, & Sibley, 2018), our findings suggest the importance of studying both empathic as well as counter-empathic emotions in groups.…”
Section: Discussionmentioning
confidence: 76%
“…Altemeyer (2003), for example, found that RF correlates with religious ethnocentrism (i.e., a tendency to make “ingroup vs. outgroup” judgment based on religious affiliations) and prejudice. Part of the explanation for this is that religious fundamentalists are strongly identified with their religious group (Saroglou, 2016; Ysseldyk, Matheson, & Anisman, 2010), and as proposed by social identity theory, strong ingroup identification can lead to both ingroup favoritism and intergroup discrimination (Perry, Priest, Paradies, Barlow, & Sibley, 2018; Tajfel, 1981; Tajfel & Turner, 1979).…”
Section: Rf and Ebmentioning
confidence: 99%